FUMAROLIC ACTIVITY OF AVACHINSKY AND KORYAKSKY VOLCANOES, KAMCHATKA, FROM 1993 TO 1994 - Taran Y.A.; Shapar V.N.; Ovsyannikov A.A.; Bilichenko A.A.; Connor C.B. (My University, 1997)
Volcanic gas and condensate samples were collected in 1993–1994 from fumaroles of Koryaksky and Avachinsky, basaltic andesite volcanoes on the Kamchatka Peninsula near Petropavlovsk–Kamchatsky. The highest-temperature fumarolic discharges, 220  °C at Koryaksky and 473  °C at Avachinsky, are water-rich (940–985 mmol/mol of H2O) and have chemical and isotopic characteristics typical of Kamchatka–Kurile, high- and medium-temperature volcanic gases. The temperature and chemical and water isotopic compositions of the Koryaksky gases have not changed during the past 11 years. They represent an approximate 2 : 1 mixture of magmatic and meteoric end members. Low-temperature, near-boiling-point discharges of Avachinsky Volcano are water poor (≈880 mmol/mol); Their compositions have not changed since the 1991 eruption, and are suggested to be derived from partially condensed magmatic gases at shallow depth. Based on a simple model involving mixing and single-step steam separation, low water and high CO2 contents, as well as the observed Cl concentration and water isotopic composition in low-temperature discharges, are the result of near-surface boiling of a brine composed of the almost pure condensed magmatic gas. High methane content in low-temperature Avachinsky gases and the 220  °C Koryaksky fumarole, low C isotopic ratio in CO2 at Koryaksky (–11.8‰), and water isotope data suggest that the "meteoric" end member contains considerable amounts of the regional methane-rich thermal water discovered in the vicinity of both volcanoes.